2015
DOI: 10.1016/j.jamda.2015.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Effects of an Ambulatory Geriatric Unit (the AGe-FIT Study): A Randomized Controlled Trial

Abstract: clinicaltrials.gov identifier: NCT01446757.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 35 publications
2
81
1
Order By: Relevance
“…The main outcomes from the AGe-FIT study showed that interdisciplinary care at an AGU, based on CGA, reduced days in hospital and increased the participants' sense of security in care interaction without increasing costs (Ekdahl et al 2015). It did not reduce symptom prevalence or symptom burden.…”
Section: Msas Subscale Scoresmentioning
confidence: 95%
See 2 more Smart Citations
“…The main outcomes from the AGe-FIT study showed that interdisciplinary care at an AGU, based on CGA, reduced days in hospital and increased the participants' sense of security in care interaction without increasing costs (Ekdahl et al 2015). It did not reduce symptom prevalence or symptom burden.…”
Section: Msas Subscale Scoresmentioning
confidence: 95%
“…Assessment -a Frailty Intervention (AGe-FIT) (Ekdahl et al 2015). The study hypothesis of the Age-FIT was that the care based on CGA provided by an ambulatory geriatric outpatient clinic would reduce hospitalization (primary outcome) compared with usual care.…”
Section: Symptom Management Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Of note, in the results section of our review, we described the reduction in length of stay correctly. We have corrected Table 4 for inclusion as an erratum and include several edits for improved clarity.…”
Section: R Ekdahl Correctly Points Out That Inmentioning
confidence: 98%
“…The Geriatric Department at the hospital had a memory clinic and an orthogeriatric ward. The study protocol and results on the primary outcome (number of hospitalizations), other health-related outcomes and cost effectiveness have previously been published [14][15][16][17].…”
Section: Study Design and Settingmentioning
confidence: 99%